Prisoners' work and vocational training - Simon, Frances H. (Routledge, 1999)
"Most prisoners serving in British prisons are required to work. Does this work help them to serve their sentences, and does it help them to get employment when they are released?" "Prisoners' Work and Vocational Training portrays the various kinds of work and vocational training courses provided for prison inmates, and compares them with work and training outside prison. It describes what satisfactions and responsibilities the prisoners get - or do not get - in their work and how the process is viewed by the staff who supervise them. A significant part relates prisoners' experiences of work to their efforts to find jobs after being released, and shows that the link between unemployment and crime, while real, is not simple." "Prisoners' Work and Vocational Training is essential reading for those studying criminology, prison and probation studies as well as for prison staff, probation officers, social workers and careers advisers."--Jacket